Residential suburbanisation in the hinterland of Bratislava – a case study of municipalities in the Austrian border area - Renáta Farkas; Michal Klobučník (Hungarian Geographical Bulletin, 2021)
This paper provides an overview of the process of residential suburbanisation in the hinterland of Bratislava. The study focuses on the municipalities around the Austrian border area. The main aim of the paper is to investigate the characteristics of cross-border suburbanisation, which is a significant spatial phenomenon in the municipalities of northern Burgenland and the south-eastern part of Lower Austria. The analysis has a spatio-temporal dimension, as it depicts the time-space characteristics of the phenomenon – both for a single time point, as well as for a time series from the approximate beginning of the onset of suburbanisation up to the present. While monitoring the growth of the number of Slovaks in the study area, we observed a gradual increase in all the selected municipalities of the Austrian border area, with the distance from Bratislava being a significant factor here. The analysis of migration in the surveyed municipalities showed predominantly positive migration efficiency – immigration was negated by emigration only to a small extent (compared to suburbanisation in the Slovak hinterland of Bratislava, which is, however, relatively high). The structural characteristics of Slovak immigrants, where the younger age group of 30 to 44 years followed by a child component up to 14 years predominated, attest to the ongoing process of suburbanisation. The research confirmed the advancing residential suburbanisation and expansion of the cross-border suburban hinterland of Bratislava.